Climate change adaptation and disaster risk reduction in urban development plans for resilient cities - Wan Mohd Rani, Wan Nurul Mardiah; Kamarudin, Khairul Hisyam; Razak, Khamarrul Azahari; Asmawi, M. Zainora (IOP Publishing, 2020)
As a result of climate change, cities today are increasingly exposed to various climate-related risks. This has resulted in a significant change in the way we deal with cities. In recent years, efforts toward achieving resilient cities have been strengthened with various initiatives and actions. Internationally, among the key initiatives are the launching of Sustainable Development Goals, New Urban Agenda, and Sendai Framework for Disaster Risk Reduction, the Paris Agreement to achieve climate and disaster resilient within cities. Development plans are known to be essential documents to present strategies to guide future development, thus have the potential to ensure the improvement of the city's resilience. Hence, this paper aimed at assessing the current state of the adoption of climate change adaptation and disaster risk reduction strategies in the various level of development planning. Based on the content analysis method, the paper discusses the different types of adaptation and mitigation interventions at national, state and local level plans aimed at reducing the impact of climate change and disaster risk in cities. Malaysian's federal policy documents (Eleventh Malaysia Plan, National Physical Plan III and National Urbanisation Policy II), state structure plans (Kuala Lumpur Structure Plan 2020 and Pahang State Structure Plan 2035) and local development plans (Kuala Lumpur City Plan 2030 and Cameron Highlands Draft Local Plan 2030) were referred to for this purpose. Overall, findings of the study indicated that at the national level, aspects of CCA and DRR are limited to the environment and infrastructure sector. However, locally, much higher integration of CCA and DRR strategies are evident in the Cameron Highlands Draft Local Plan 2030. Thus, it is realised that Malaysia is progressing positively towards mainstreaming CCA and DRR strategy in the different level of development plans crossing all sectors with various types of interventions. However, more effort is needed to focus on the collaborative action in the implementation of the strategies and actions stipulated in the development plans.